Juridical Review of the Legal Protection of Notary Employees as Witness Instrumenter in Making Deeds - Munthe, M.Alvicki; Purba, Hasim; Suprayitno (Law and Economics, 2025)
A notary, as a public official authorized to draw up authentic deeds, requires the assistance of notary employees who also serve as instrumental witnesses in the deed-making process. Instrumental witnesses are responsible for witnessing the reading and signing of the deed, as regulated in Article 16 paragraph (1) letter i and Article 40 of the Law on Notary Position (UUJN). This study employs a normative juridical method with a descriptive-analytical approach, using secondary data obtained through literature review and document study. The findings show: first, the role of instrumental witnesses is crucial because if not fulfilled, the deed only holds evidentiary power as a private deed (Article 41 UUJN). Second, notary employees serving as instrumental witnesses bear criminal and civil liability for any misuse of deed confidentiality, and the obligation to maintain such confidentiality is lifelong. Third, although specific legal protection for notary employees as instrumental witnesses is not regulated in the UUJN, general protection is provided under the Manpower Law and the Witness and Victim Protection Law, especially regarding testimony in criminal proceedings, including protection from coercion, the right to legal counsel, and other general safeguards